Clinical case review: out-of-hospital cardiac arrest following thyroid storm. (2nd April 2021) - Hale, Matthew; Mildenhall, Jo; Hook, Christopher; Burt, James
Abstract : Acute thyrotoxicosis (thyroid storm) caused by hyperthyroidism is a rare but severe endocrine imbalance which, in extreme cases, may lead to ventricular fibrillation and ultimately, without intervention, death. The authors attended such an incident and, following clinical interventions, achieved return of spontaneous circulation with a good outcome for the patient and subsequent hospital discharge.